1995
DOI: 10.1128/jb.177.6.1425-1434.1995
|View full text |Cite
|
Sign up to set email alerts
|

Control of transcription termination by an RNA factor in bacteriophage P4 immunity: identification of the target sites

Abstract: Prophage P4 immunity is elicited by a short, 69-nucleotide RNA (CI RNA) coded for within the untranslated leader region of the same operon it controls. CI RNA causes termination of transcription that starts at the promoter P LE and prevents the expression of the distal part of the operon that codes for P4 replication functions (␣ operon). In this work, we identify two sequences in the untranslated leader region of the ␣ operon, seqA and seqC, that are the targets of the P4 immunity factor. seqA and seqC exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 32 publications
4
54
0
Order By: Relevance
“…ysis of the HinfI/BamHI fragment indicated that it was predicted to contain the following P4 TT features (Allison and Verma, unpublished): the P LE 70 promoter (Ϫ35 sequence, TTGATT, nt 27568 to 27573; Ϫ10 sequence, TACACT, nt 27591 to 27596); cI RNA containing seqA, seqB, seqCЈ, and seqCЉ and folding in the conserved secondary RNA structure of the P4 cI RNA; and a nested ORF, orf-77, commencing downstream of the cI RNA (the ATG start codon is located at nt 27846) and reading in frame with orf-37. In the immune state of phage P4, the cI RNA molecule (69 nt), which is the product of processing of a transcript initiated from constitutive promoter P LE , mediates TT and superinfection immunity through RNA-RNA interactions with complementary sequences located up-and downstream in the nascent transcript, thus directly preventing the expression of downstream genes involved in the lytic cycle (14,42). The cI RNA has a complex predicted secondary structure and contains seqB, which is complementary to upstream seqA and downstream seqCЈ and seqCЉ (14,42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ysis of the HinfI/BamHI fragment indicated that it was predicted to contain the following P4 TT features (Allison and Verma, unpublished): the P LE 70 promoter (Ϫ35 sequence, TTGATT, nt 27568 to 27573; Ϫ10 sequence, TACACT, nt 27591 to 27596); cI RNA containing seqA, seqB, seqCЈ, and seqCЉ and folding in the conserved secondary RNA structure of the P4 cI RNA; and a nested ORF, orf-77, commencing downstream of the cI RNA (the ATG start codon is located at nt 27846) and reading in frame with orf-37. In the immune state of phage P4, the cI RNA molecule (69 nt), which is the product of processing of a transcript initiated from constitutive promoter P LE , mediates TT and superinfection immunity through RNA-RNA interactions with complementary sequences located up-and downstream in the nascent transcript, thus directly preventing the expression of downstream genes involved in the lytic cycle (14,42). The cI RNA has a complex predicted secondary structure and contains seqB, which is complementary to upstream seqA and downstream seqCЈ and seqCЉ (14,42).…”
Section: Resultsmentioning
confidence: 99%
“…In the immune state of phage P4, the cI RNA molecule (69 nt), which is the product of processing of a transcript initiated from constitutive promoter P LE , mediates TT and superinfection immunity through RNA-RNA interactions with complementary sequences located up-and downstream in the nascent transcript, thus directly preventing the expression of downstream genes involved in the lytic cycle (14,42). The cI RNA has a complex predicted secondary structure and contains seqB, which is complementary to upstream seqA and downstream seqCЈ and seqCЉ (14,42). P LE , seqA, seqB, and seqC are located within the eta gene.…”
Section: Resultsmentioning
confidence: 99%
“…The waaL::cam locus was transferred into FL905, FL907, AM661, and AM679 by P1 transduction (34). Bacteria were grown in LD broth (33). When required, 0.2% L-arabinose (as an inducer of the araBp promoter), 0.2% glucose, 0.5 mM isopropyl-␤-D-thiogalactopyranoside (IPTG) for overexpression of LptC with a C-terminal His 6 tag (LptC-H) or 1 mM IPTG, 100 g/ml ampicillin, 50 g/ml kanamycin, and 25 g/ml chloramphenicol were added.…”
Section: Methodsmentioning
confidence: 99%
“…E. coli XL1-Blue (5) was grown in LD medium (28) supplemented, when necessary, with kanamycin (50 g/ml). M. smegmatis mc 2 155 was grown in LD medium containing 0.2% (vol/vol) glycerol and 0.05% (vol/vol) Tween 80 and supplemented when necessary with kanamycin (20 g/ml).…”
Section: Methodsmentioning
confidence: 99%